Non-febrile Seizure Associated with Pericallosal Lipoma - Mehmet Davutoglu; Yakup Yesil; Abdulkadir Asan; Hikmet Dolu; Hamza Karabiber (Elsevier, 2008)
Intracranial lipoma is a very rare condition, with an incidence of less than 0.1% of all intracranial tumors. They are mostly localized in the pericallosal region. Pericallosal lipoma is an extremely rare tumor of the central nervous system and rarely gives any symptoms. A 6-year-old girl with an unexplained headache was admitted to the Pediatric Outpatient Clinic with complaints of non-febrile seizure. Her seizure was a complex-partial type. Biochemical tests for seizure etiology did not reveal any specific cause. Electroencephalography (EEG) revealed typical epileptic activity. Magnetic resonance imaging (MRI) gave images of a mass approximately 1 cm in diameter in the vicinity of corpus callosum splenium. Her seizures were kept under control with carbamazepine (400 mg/day) and indicators of neuromotor development were found to be normal throughout 24-month period of follow up. Even though it is a rare condition, pericallosal lipoma should also be taken into account in the differential diagnosis of non-febrile seizures in children.